Legal Analysis of Legal Protection of the Rights of Employees with Fixed-Term Employment Agreements (PKWT) Who Receive Unilateral Termination of Employment (PHK) by the Company (Research Study in Semarang City) - Sasongko, Unggul Agus; Arpangi, Arpangi (UNISSULA Semarang, 2025)
Abstract. Fixed-Term Employment Agreement is a form of employment relationship that is widely used in Indonesia, especially for temporary work. Although it has been regulated in Law Number 6 of 2023 and Government Regulation Number 35 of 2021,Fixed-Term Employment Agreement employees often face legal vulnerabilities, especially when there is a unilateral Termination of Employment before the end of the contract period. Unilateral layoffs without a clear legal basis not only violate aplicable provisions but also have a significant impact on workers' welfare. The settlement mechanism through the Industrial Relations Court that is available is often ineffective in providing justice quickly. Weak supervision, lack of understanding of the law by workers, and bad faith from companies worsen this situation. Based on the views of legal experts, fair and effective legal protection is essential to ensure social justice in accordance with the values of Pancasila. Therefore, this study was conducted to analyze the legal protection of Fixed-Term Employment Agreement employees who were unilaterally laid off by companies in Semarang City. The research method used is legal research with a sociological juridical aproach (empirical), which combines normative analysis with empirical data obtained from the field. The author conducted an analysis of legal protection for Fixed-Term Employment Agreement employees who were unilaterally laid off by companies in Semarang City and the aplication of the law on the rights of Fixed-Term Employment Agreement employees who were unilaterally laid off by companies in Semarang City. Legal protection forFixed-Term Employment Agreement workers includes preventive protection, namely through the creation of a complete and transparent written work contract, as well as repressive protection through dispute resolution mechanisms such as bipartite, mediation, and the Industrial Relations Court. The views of legal experts such as Philipus M. Hadjon, Satjipto Rahardjo, Hans Kelsen, Yudi Latif, and Lawrence M. Friedman reinforce the importance of fair legal protection that sides with workers as the weaker party.